Lamivudine therapy during the second vs the third trimester for preventing transmission of chronic hepatitis B. Issue 3 (26th December 2016) - Pan, C. Q.; Yi, W.; Liu, M.; Wan, G.; Hu, Y.‐H.; Zhou, M.‐F.
Summary: There are little data on the timing of initiating lamivudine therapy for preventing transmission of hepatitis B in highly viremic mothers. Between May 2008 and January 2015, we retrospectively enrolled mothers with HBV DNA >6 log10  copies/mL who received lamivudine during pregnancy, and we compared them to untreated mothers. The primary measurement was the vertical transmission rate. The secondary outcomes were the mothers' and infants' safety. Among 249 consecutive mothers enrolled, 66 and 94 received lamivudine during the second and third trimesters, respectively, and 89 were untreated. At delivery, maternal mean HBV DNA levels were significantly lower in mothers who received lamivudine (4.45 log10; vs 7.16 log10  copies/mL; P <.001). Lamivudine treatment was well tolerated. However, early treatment during the second trimester did not significantly increase the percentage of mothers achieving HBV DNA levels of <6 log10  copies/mL compared to those treated during the third trimester (98.5% vs 94.7%; P =.40). At the age of 28 weeks, the vertical transmission rates were significantly lower in the lamivudine‐treated mothers vs in the untreated mothers (0% [0/160] vs 5.62% [5/89]; P <.001), but the rates were similar when comparing the two subgroups treated with lamivudine (0% [0/66] vs 0% [0/94], P >.05). The birth defect rates and mothers' and infants' adverse events were similar among the groups. Lamivudine treatment initiated in the second or third trimester for mothers with HBV DNA levels below 9 log10  copies/mL was equally safe and effective in preventing vertical transmission. Thus, lamivudine should be deferred until the third trimester to minimize foetal exposure and drug resistance.